The Dynamics of the 2024 Jakarta Gubernatorial Election: Political Competition, Electoral Challenges, and Democratic Prospects - Salsabila, Ulfa; Fatimah, Siti; Alfarisi, Muhammad Adib (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study examines the dynamics of the 2024 Jakarta Gubernatorial Election (Pilkada). The focus is on the complex competition between political parties and candidates, as well as the winning strategy of the candidate pair Pramono Anung and Rano Karno in the 2024 Jakarta Pilkada. Based on the dynamics and controversies surrounding the 2024 Jakarta Pilkada, this research aims to assess the prospects for democracy in the organization of the Jakarta Pilkada in general, based on the indicators of good electoral governance. This paper uses a normative legal research method with secondary data collection techniques through literature studies. The findings of this study show that the Jakarta Pilkada was conducted democratically as it implemented the indicators of good electoral governance. However, these indicators have not been fully implemented, such as the low participation of Jakarta residents in the 2024 Pilkada, the proper distribution of Form C6, and the misinformation spread by the General Election Commission (KPU) regarding the quick count survey results and the Sirekap system, which caused public confusion. This article is expected to provide in-depth insights for readers on the dynamics of the 2024 Jakarta Pilkada. Furthermore, this study is also intended to serve as an evaluation and reflection for stakeholders to improve the organization of future Pilkada that is more democratic and accountable. [Penelitian ini mengulas dinamika Pilkada Jakarta tahun 2024. Fokusnya adalah pada dinamika persaingan yang cukup kompleks antara partai politik dan pasangan calon, serta strategi kemenangan pasangan Pramono Anung dan Rano Karno pada Pilkada Jakarta tahun 2024. Berangkat dari dinamika dan polemik Pilkada Jakarta 2024, penelitian ini bertujuan untuk mengkaji prospek demokrasi pada penyelenggaran Pilkada Jakarta secara umum berdasarkan indikator good electoral governance. Tulisan ini menggunakan metode penelitian hukum normatif dengan teknik pengumpulan data sekunder melalui studi pustaka. Hasil penelitian ini menunjukkan bahwa Pilkada Jakarta berlangsung secara demokratis karena telah mengimplementasikan indikator good electoral governance. Meskipun demikian, indikator-indikator tersebut belum terimplementasi dengan sempurna, seperti rendahnya partisipasi masyarakat Jakarta pada Pilkada Jakarta tahun 2024, formulir C6 yang terdistribusi dengan baik, serta disinformasi yang dilakukan oleh KPU terkait hasil survei quick count dan Sirekap yang menimbulkan kebingungan publik. Artikel ini diharapkan dapat memberikan wawasan mendalam bagi pembaca tentang dinamika Pilkada Jakarta tahun 2024. Selain itu, penelitian ini juga diharapkan dapat menjadi bahan evaluasi dan refleksi bagi para skateholders dalam meningkatkan penyelenggaraan Pilkada yang lebih demokratis dan akuntabel di masa depan].